Why Patients Should Give Thanks for Their Disease: Traditional Christianity on the Joy of Suffering - Hayes, Cornelia (Christian bioethics, 2006)
Patristic teaching about sin and disease allows supplementing well-acknowledged conditions for a Christian medicine with further personal challenges, widely disregarded in Western Christianities. A proper appreciation of man's vocation toward (not just achieving forgiveness but) deification reveals the need to cooperate with the Holy Spirit's offer of grace toward restoring man's prefallen nature. Ascetical exercises designed at re-establishing the spirit's mastery over the soul distance persons from (even supposedly harmless) passion. They thus inspire the struggle towards emulating Christ's (self-crucifying) kenotic love, and to accept even secularly “undeserved” suffering as spiritually deserved in view of his (forever) lacking fervor in that struggle. Only in the spirit of that love can the evil Adam's sin brought into this world work its therapeutic impact, the eschatological purpose of which explains God's lovingly permitting that evil. This therapeutic impact is physically manifested already in this life through the transforming energies granted the saints of the church.